1980
DOI: 10.1128/aac.18.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cefmetazole in normal subjects and in patients with impaired renal function

Abstract: The pharmacokinetics of cefimetazole, a new cephamycin antibiotic, were examined after a 1-h intravenous drip infusion of 1 g to 5 healthy volunteers with normal renal function and 16 Group 1 was composed of five healthy volunteers with creatinine clearances of 95.6 to 155.6 ml/min. Group 2 was composed of four patients with creatinine clearances of 65.5 to 86.8 ml/min. In group 3 were four patients with creatinine clearances of 35.2 to 52.7 ml/ min. Group 4 had four patients with creatinine clearances of 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 12 publications
(1 reference statement)
2
19
2
Order By: Relevance
“…These differences may be a reflection of the shorter sampling time employed (only 6 h postdose), the use of different assay techniques (microbiological versus high-performance liquid chromatography), or the variability in the patient populations. Furthermore, a one-compartment model was used by Ohkawa et al (12) to fit the four postdose datum points, whereas our study utilized a two-compartment open model which provided a better fit of the plasma concentration-versus-time data for 24 of 25 subjects. Other differences include the measurement of a greater urinary recovery of intact drug in normal subjects (84%) than the previously reported mean of 69 to 71% (7,12).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These differences may be a reflection of the shorter sampling time employed (only 6 h postdose), the use of different assay techniques (microbiological versus high-performance liquid chromatography), or the variability in the patient populations. Furthermore, a one-compartment model was used by Ohkawa et al (12) to fit the four postdose datum points, whereas our study utilized a two-compartment open model which provided a better fit of the plasma concentration-versus-time data for 24 of 25 subjects. Other differences include the measurement of a greater urinary recovery of intact drug in normal subjects (84%) than the previously reported mean of 69 to 71% (7,12).…”
Section: Resultsmentioning
confidence: 99%
“…All the subjects recovered with no sequelae. All abnormal laboratory tests (i.e., mild partial thromboplastin time elevation [n Ohkawa et al (12) evaluated the pharmacokinetics of cefmetazole in 21 subjects with normal (CLCR, >90 ml/min per 1.73 m2) and decreased (CLCR, 60 to 90, 30 to 59, and 10 to 29 ml/min per 1.73 m2) renal function. As in the present study, these investigators observed an unchanged V,s, a decreased CLp, and an increased t1/2, with declining renal function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cefmetazole pharmacokinetics have also been studied in patients with various degrees of renal insufficiency (13,20). In these patients, the elimination half-life of cefmetazole was found to increase progressively with decreasing renal function.…”
mentioning
confidence: 99%